Análise técnica e econômica do armazenamento de hidrogênio por processo de compressão - Araujo, Fernando Henrique Mayworm de [UNESP] (2016)
The rapid increase in world population and increasing technological development in recent decades are generating a deficit between world energy production and consumption. The weather effects related to the use of fossil fuels traditionally used (worldwide) in energy production, and the possibility of exhaustion accelerate research and development of new forms of clean and renewable energy production. An important alternative energy source is hydrogen. Its production from renewable energy sources reduces the environmental impact caused by greenhouse gas emissions from the use of fossil fuels. This work carried out technical and economic studies hydrogen storage obtained by electrolysis, compression process using electricity from renewable sources (wind and photovoltaic). Initially are some considerations and a literature review is made of hydrogen storage. Then, the energy analysis of the hydrogen compression is performed to determine the fraction of the stored energy is expended in the process, depending on the type produced renewable hydrogen (Solar Hydrogen or Hydrogen Wind. Following is made exergy analysis Compression and hydrogen storage, determining the exergetic efficiency of the storage process for renewable sources considered. Subsequently, makes up economic analysis process to determine the costs in US$/kWh storage for pressures of 20 and 70 MPa (commercially available compressors) considering the electricity tariff produced by photovoltaic and solar wind source. In the final phase are woven the conclusions on the energy point of view, exergetic and economic.